Context-Dependence, Perspective and Relativity - Recanati, Francois; Stojanovic, Isidora; Villanueva, Neftali (De Gruyter, 2010)
This volume brings together original papers by linguists and philosophers on the role of context and perspective in language and thought. Several contributions are concerned with the contextualism/relativism debate, which has loomed large in recent philosophical discussions. In a substantial introduction, the editors survey the field and map out the relevant issues and positions.